ENERGY SYSTEMS EFFICIENCY INFLUENCES THE RESULTS OF 2,000 M RACE SIMULATION AMONG ELITE ROWERS - Martin, Stefan Adrian; Tomescu, Valeriu (Medicine and Pharmacy Reports, 2017)
Hypothesis. Energy efficiency within an elite group of athletes will ensure metabolic adaptation during training. Objectives. To identify energy system efficiency and contribution according to exercise intensity, and performance obtained during a 2,000 m race simulation in an elite group of rowers. Method. An observational cross-sectional study was conducted in February 2016 in Bucharest, Romania, on a group of 16 elite rowers. Measurements were performed through Cosmed Quark CPET equipment, and Concept 2 ergometer, by conducting a VO2max test over a standard rowing distance of 2,000 m. The analyzed parameters during the test were: HR (bpm), Rf (b/min), VE (l/min), VO2 (ml/min), VCO2 (ml/min), VT (l), O2exp (ml), CO2exp (ml), RER, PaCO2 (mmHg), PaO2 (mmHg), Kcal/min, FAT (g), CHO (g), from which we determined the ventilatory thresholds, and the energy resource used during the specific 2,000 m rowing distance (ATP, ATP+CP, muscle glycogen). Results. We performed an association between HR (180.2±4.80 b/min), and carbohydrate consumption during the sustained effort (41.55±3.99 g) towards determining the energy systems involved: ATP (3.49±1.55%), ATP+CP (18.06±2.99%), muscle glycogen (77.9±3.39%). As a result, completion time (366.3±10.25 s) was significantly correlated with both Rf (p=0.0024), and VO2 (p=0.0166) being also pointed out that ≥5 l VO2 value is associated with an effort time of ≤360 s. (p=0.040, RR=3.50, CI95%=1.02 to 11.96). Thus, the average activation time among muscle ATP (12.81±5.70 s), ATP+CP (66.04±10.17 s, and muscle glycogen (295±9.5 s) are interrelated, and significantly correlated with respiratory parameters. Conclusions. Decreased total activity time was associated with accessing primary energy source in less time, during effort, improving the body energy power. Its effectiveness was recorded by early carbohydrates access, as a primary energy source, during specific activity performed up to 366 seconds.